"The Cost and Efficiency of Distribution in the Soviet Union": Comment - Ross, Myron H. (Quarterly Journal of Economics, 1963)
Journal Article “The Cost and Efficiency of Distribution in the Soviet Union”: Comment Get access Myron H. Ross Myron H. Ross Western Michigan University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 77, Issue 3, August 1963, Pages 503–504, https://doi.org/10.2307/1879575 Published: 01 August 1963